Physiotherapy Management in Dupuytren's Contracture and Post-Burn Injury with TENS, Ultrasound, Scar Massage, and Exercise Modalities: A Case Study - Ribka Vlorentyna Wilger; Arin Supriyadi; Nilam Nur Hamidah (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Intoduction: Dupuytren’s Contracture et causa post burn injury is a condition characterized by fibrosis and contracture of the palmar fascia following burn trauma which causes pain, limited joint range of motion, decreased muscle strength, impaired skin integrity, and reduced functional activity. Objective: to determine the effectiveness of physiotherapy management using Transcutaneous Electrical Nerve Stimulation (TENS), ultrasound, scar massage, and exercise in patients with Dupuytren’s Contracture et causa post burn injury. Methods: the research method used a case study conducted on one 56 year old male patient diagnosed with Dupuytren’s Contracture et causa post burn injury. The measurement tools used included the Numeric Rating Scale (NRS) for pain assessment, goniometer for measuring joint range of motion, Manual Muscle Testing (MMT) for muscle strength, Vancouver Scar Scale (VSS) for scar evaluation, SWEAT for skin integrity assessment, and Wrist and Hand Disability Index (WHDI) for evaluating functional ability. Results and Discussion: after three sessions of physiotherapy intervention, the patient showed decreased pain intensity, increased joint range of motion, improved skin sensitivity, and slight improvement in functional activity, although muscle strength and scar characteristics showed no significant changes. Conclusion: physiotherapy interventions consisting of TENS, ultrasound, scar massage, and exercise were effective in reducing pain and improving functional ability in cases of Dupuytren’s Contracture et causa post burn injury